Social and Economic Barriers to Exclusive Breastfeeding in Rural Zimbabwe - Munyaradzi Muchacha, BSW; Edmos Mtetwa, MSc (Global Health and Education Projects, Inc., 2014)
Objectives: Exclusive breast feeding (EBF) uptake in Zimbabwe is very low. Given that EBF is a physiological process which transpires in a specific socio-economic milieu, this study investigates the socio-economic factors militating against its uptake. Methods: The study used a mixed research methodology. The concurrent nested model of mixed methods was utilized using one data collection phase, during which both quantitative and qualitative data were collected simultaneously. Results: The research noted that factors such as low education, low income, gender inequalities, social influence, and traditional practices were hindering the uptake of exclusive breast feeding. Conclusions and Global Health Implications: The study envisages that it is pertinent for infant feeding programs to address socio- economic barriers to EBF in order to influence a positive uptake. The potential interventions include increasing men's involvement, raising awareness on EBF, and strengthening the Village Health Worker Program.